HUBUNGAN KEBIASAAN MINUM KOPI DENGAN KADAR HEMOGLOBIN PADA PENGUNJUNG KEDAI “SEDERHANA KOPI” SURAKARTA - Gilang Firmansyah Hidayat; Endang Widhiyastuti (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2022)
Consumption of coffee in Indonesia has increased every year. This is what makes the trend of coffee drinkers continue to increase. There are caffeine in coffee which are an iron absorption inhibitor where caffeine binds iron so it cannot be absorbed by the body. Iron was required in the synthesis of hemoglobin. Reduced hemoglobin levels can cause anemia. The limit of male hemoglobin levels for diagnosing anemia is when the hemoglobin level was less than 13 g/dl. This study aims to determine the relationship between habits drinking of coffee with hemoglobin levels in visitors to the